2018
DOI: 10.13187/er.2018.4.298
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges Facing Bosnian High-School EFL Learners

Abstract: The importance of learning English as a second or foreign language has been globally recognized, as its presence is plainly evident in diverse areas, in the area of business and science in particular (Schütz, 2005). Thus, as a global lingua franca, the English language is taught as the first foreign language in non-English-speaking countries around the world, and likewise it is fairly widespread as a compulsory course in elementary and secondary schools in Bosnia and Herzegovina. According to the curriculum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…In this way, students are not exposed to English but rather learn about it. This fact is in line with the investigations of Kovačević, Brdarević-Čeljo & Bećirović (2018), who, concerning the way the English language is taught in B&H, found that the students are not satisfied with the teaching methods, indicating that more focus should be placed on speaking and reading skills instead of grammar and translation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this way, students are not exposed to English but rather learn about it. This fact is in line with the investigations of Kovačević, Brdarević-Čeljo & Bećirović (2018), who, concerning the way the English language is taught in B&H, found that the students are not satisfied with the teaching methods, indicating that more focus should be placed on speaking and reading skills instead of grammar and translation.…”
Section: Discussionsupporting
confidence: 84%
“…However, even though it is a common foreign language taught through the years of primary and secondary schools, according to Kovačević, Brdarević-Čeljo & Bećirović (2018), students are not satisfied with the EL teaching methods, lacking more focus on speaking and reading skills instead of grammar and translation. Since very little has been done in the past to investigate how Bosnian students are taught the English language, this study will examine which method or methods English language teachers in several Bosnian primary and secondary schools prefer and how they see their students' preferences for the two most common and used language teaching methods (Grammar-translation method and Direct method).…”
Section: English Language In Bandhmentioning
confidence: 99%
“…Namely, the current study participants genuinely want to learn English, due to its global use and expansion in various international domains, and they consider it a useful tool for their future academic and professional achievements. In addition to this, the importance of obtaining higher English language proficiency is constantly emphasized and the English language course is an obligatory course throughout elementary and high-school education in Bosnia and Herzegovina (Bećirović, 2017;Brdarević-Čeljo et al, 2018;Brdarević-Čeljo et al, 2021;Dubravac, 2018;Dubravac et al, 2018;Kovačević et al, 2018;Laličić & Dubravac, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study aims to provide a more detailed analysis by taking into consideration three different variables that may be determinative in the construction of LLBs; namely, gender, educational level, and grades of students in Bosnia and Herzegovina. Despite different studies related to the process of EFL learning having been conducted in this sociocultural context, such as the studies measuring the impact of diverse factors on students' English language proficiency as well as the proficiency itself (Brdarević-Čeljo et al, 2018;Delić et al, 2018;Habibić & Dubravac, 2016;Kovačević et al, 2018;Rizvić & Bećirović, 2017) and their use of learning/reading strategies Brdarević-Čeljo & Asotić, 2017;Tankosić & Dubravac, 2016), studies exploring learners' LLBs are quite rare. Thus, one of the studies explored the state of LLBs among high-school students (Ozturk & Turkyilmaz, 2014), another one investigating the correlation between the beliefs and language learning strategies (Akbarov & Kovačević, 2015), and finally, the relationship between LLBs and the complexity of syntactic structures used by language learners (Kovačević, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%